Persistent plants that cause damage to crops of family farmers in Agreste region of Alagoas / Plantas invasoras persistentes em culturas cultivadas por agricultores familiares na região agreste de Alagoas - Luan Lucas Cardoso Lima; Luiz Eduardo Bezerra Silva; João Pedro Ferreira Barbosa; Rafael Lima Vieira dos Santos; Dacio Rocha Brito (Universidade Estadual de Alagoas, 2018)
Undesirable plants are one of the main problems encountered by farmers, because they are not known and also not know the correct measures to control them. This work objected identified the plants that remain in the crops of small producers after a third clean, whose cultivation are done manually, To identify the invasive plants, was used in a hollow frame of wood with a dimension of 0.75 m², which was played four times randomly in the study area. In addition to removing the undesirable plants, photographic records were made to aid the identification of plants. It was found that after three cleanings made by the farmer, some species persisted before harvesting the planted crops. Using the method of Kuva et al. (2000), five species of plants were found to continue in the plantations after a third clean. The species Mollugo verticallata L. and Euphorbia hirta L. were more frequently in the area. A questionnaire was also applied to the farmers, where the need for further research was identified to select better methods or control method.